Three Little Words and the Critical Argument of The Best Show on WFMU - Thomas Britt (Angles)
Tom Scharpling was the longtime host (October 2000 - December 2013) of The Best Show on WFMU, a music/comedy program that originated on listener-supported New Jersey radio station WFMU and became internationally popular through Internet streaming and podcasting. My paper examines the ways in which “Rock, Rot & Rule,” the sketch that inspired the program, utilizes brevity to satirize the dilemma of criticism. Scharpling interviewed Ronald Thomas Clontle, author of a book titled Rock, Rot & Rule, “the ultimate argument settler,” whose function is to categorize popular music into acts that rock, acts that rot, and acts that rule. The premise of Clontle’s book involves comedic devices like overstatement and simplification. The irony of Clontle’s claim to settle arguments is that his interview has the opposite effect. It infuriates listeners. Impassioned music enthusiasts call in to criticize his methodology, but he cannot be bothered. Unbeknownst to listeners, Clontle is a character played by musician Jon Wurster. He and Scharpling have intricately scripted their interaction, creating a comedy of outrage among people who take music seriously. And therein lies the value of “Rock, Rot & Rule” as an influential instance of brevity in humor. For the unsuspecting listeners of “Rock, Rot & Rule,” Clontle arouses anxiety because he is indicative of the future of criticism.